Estimated Divergence Times of Lecanicillium in the Family Cordycipitaceae Provide Insights Into the Attribution of Lecanicillium - Zhou, Ye-Ming; Zhi, Jun-Rui; Qu, Jiao-Jiao; Zou, Xiao (Frontiers in Microbiology, 2022)
Background: The genus Lecanicillium W.Gams & Zare are famous insect pathogen and are found parasitizing various hosts including arthropods, nematodes, plants, and fungi. In the new classification system, Lecanicillium was be reject and only several species be transferred to Akanthomyces. The attribution problem of the majority species in the original Lecanicillium was unsolved. To obtain a better understanding of the pivotal internal phylogeny in Lecanicillium, we estimated the divergence times of Lecanicillium to provide more insight into current status this genus within Cordycipitaceae. Results: Dating analyses support the supposition that the ancestor of the Lecanicillium was in the Cretaceous (84.36 Mya, 95% HPD: 72.12-94.74 Mya). After origin from a common ancestor, eight clades of Lecanicillium were derived and evolved independently in parallel with other genus of Cordycipitaceae. Based on the clear divergence age estimates, Lecanicillium clade 8 originated earlier as an independent group in the Cretaceous (75.61 Mya, 95% HPD: 63.31-87.54 Mya). Lecanicillium clade1-7 originated leater as an independent group in the boundary of Cretaceous and Paleogene (64.66 Mya, 95% HPD: 52.75-76.74 Mya). Lecanicillium huhutii formed an independent branch in a polytomy together with a clade containing L. tenuipes (BI posterior probabilities 1, ML boostrap 100%). Conclusions: Based on phylogenetic and morphological analyses, eight representative clades (four representative branchs of evolutionary history), including the clade 1 (members has relatively uniform sporulation structure which has globose heads with a higher number of conidia), clade 8 (including all members of Gamszarea), clade 2-5 (the differences of the divergence time estimations were smaller than other clades), clade 6-7 (they close to Gibellula, Hevansia and Ascopolyporus). Based on above trend, a new member of spider-pathogenic fungus, Lecanicillium huhutii, was reported. All other species (Lecanicillium pissodis, L. araneogemum, L. uredinophilum, L. nodulosum) in Lecanicillium clade 1 should be transferred to Akanthomyces. Monotypic genus parengyodontium should be merged with Gamszarea. No major lineages was noted to be correlated with the nearby Cretaceous-Tertiary extinction event, which means that the diversity of Lecanicillium is more likely to be caused by long-term environmental adaptation and coevolution with insects rather than dramatic extinction events.